2014
DOI: 10.1016/j.colsurfb.2014.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly and antimicrobial activity of long-chain amide-functionalized ionic liquids in aqueous solution

Abstract: Surface active amide-functionalized ionic liquids (ILs) consisting of a long alkyl chain (C6C14) connected to a polar head group (methylimidazolium or pyridinium cation) via an amide functional group were synthesized and their thermal stability, micellar properties and antimicrobial activity in aqueous solution investigated. The incorporation of an amide group increased the thermal stability of the functionalized ionic liquids compared to simple alkyl chain substituted ionic liquids. The surface activity and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
92
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 51 publications
10
92
0
Order By: Relevance
“…In the case of the cationic surfactant hexadecyltrimethylammonium bromide (CTAB) the effect of ILs on the surfactant cmc confirms the trend above described [8][9][10][11][12][13]. However, when IL posses surface activity as reported for long alkyl chain ionic liquids [14][15][16][17][18][19][20][21] and some short alkyl chain ILs [22,23] the ionic liquid / surfactant mixture behaves as a typical binary surfactant system [24][25][26]. In these binary systems the mixed micelle composition X 1 M as well as the  M interaction parameter quantifying the synergism can be obtained by applying the equations of the Regular Solution Theory [27].…”
Section: Introductionsupporting
confidence: 73%
“…In the case of the cationic surfactant hexadecyltrimethylammonium bromide (CTAB) the effect of ILs on the surfactant cmc confirms the trend above described [8][9][10][11][12][13]. However, when IL posses surface activity as reported for long alkyl chain ionic liquids [14][15][16][17][18][19][20][21] and some short alkyl chain ILs [22,23] the ionic liquid / surfactant mixture behaves as a typical binary surfactant system [24][25][26]. In these binary systems the mixed micelle composition X 1 M as well as the  M interaction parameter quantifying the synergism can be obtained by applying the equations of the Regular Solution Theory [27].…”
Section: Introductionsupporting
confidence: 73%
“…Photoisomerization of azobenzene from trans-form to more hydrophilic cis-form should account for the increased CMC value. 16 The results suggested the UVcontrolled self-assembly behavior of PN 427 A 10 -C.…”
Section: D15mentioning
confidence: 79%
“…Several studies have reported the antimicrobial properties of ionic liquids, although there are limited studies on biofilm control [40]. As such, the toxicity of an IL depends on cation, anion and side chain, thus modification of these groups allows designing either less or more toxic compounds.…”
Section: Effect Of Ionic Liquids On Natural Multispecies Phototrophicmentioning
confidence: 99%
“…Recently, Garcia et al, (2014) reported antimicrobial activity of amide-functionalised methylimidazolium or pyridinium ionic liquids against bacterial and fungal strains [40].…”
Section: Effect Of Ionic Liquids On Natural Multispecies Phototrophicmentioning
confidence: 99%